Nonmetric cranial variation in human skeletal remains from Armenia - Khudaverdyan, A.Yu. (Acta Biologica Szegediensis, 2012)
Nonmetric traits are frequently analyzed in the field of anthropology to measure genetic relatedness, or biodistance, within or between populations. These studies are performed under the assumption that nonmetric traits are genetically inherited. Historically, interpretations of both biological and cultural change within the Armenian Highland, have cited large-scale population movements. Biological estimates of this change have traditionally relied upon biodistance estimates, using odontologic, craniofacial measures of both deformed and nondeformed skulls. In order to evaluate whether large-scale prehistoric and historic migrations occurred in the Armenian Highland, we examine biodistance results from nonmetric cranial traits for 19 samples that represent all time periods on Armenian Highland. None of the distances between each pair of samples examined by this study were significant. These results suggest biological continuity on the Armenia populations. Biodistance results also suggest endogamy within inland populations. The broader implications of these results are discussed.